2005
DOI: 10.1002/app.20889
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior and morphology of polycaproamide (PCA)/cationic dyeable polycaproamide (CD‐PCA) polyblended filaments

Abstract: Polycaproamide (PCA) polymer and cationic dyeable polycaproamide (CD-PCA) polymer were blended mechanically in the proportions of 75/25, 50/50, and 25/75 in a melt twin-screw extruder to prepare three PCA/CD-PCA polyblended polymers. Blends of PCA and CD-PCA were spun into filaments. The molar ratio of 5-sodium sulfonate dimethyl isophthalate (5-SSDMI) for CD-PCA polymer was 1.99%. This study investigated the physical properties of PCA/CD-PCA polyblended filaments using gel permeation chromatograph (GPC), nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In a previous investigation, we reported some miscible and immiscible polymer blends. Miscible polymers included PET/CD‐PET,10 PCA/CD‐PCA,11 and PTT/CD‐PTT 12. Immiscible polymers included PCPL/CD‐PET,13 PA 6/m‐iPP,14 PTT/MIPP,15 CD‐PET/m‐iPP,16 and CD‐PTT/m‐iPP 17.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous investigation, we reported some miscible and immiscible polymer blends. Miscible polymers included PET/CD‐PET,10 PCA/CD‐PCA,11 and PTT/CD‐PTT 12. Immiscible polymers included PCPL/CD‐PET,13 PA 6/m‐iPP,14 PTT/MIPP,15 CD‐PET/m‐iPP,16 and CD‐PTT/m‐iPP 17.…”
Section: Introductionmentioning
confidence: 99%
“…Heidemann noted that the radius of the fi bres declined as the concentration of aqueous NaOH solution increased 9 . Hsiao et al found that the kinetics of alkaline hydrolysis of the PET/CDPET polyblended hollow fi bre resembled that of PET hollow fi bres [10][11][12][13][14][15] . The natural fi bre cotton is very comfortable for clothing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…There are some reports on the physical properties of polyamide 6 (PA 6) with other polymers such as poly(ethylene terephthalate), cationic dyeable poly(ethylene terephthalate), poly(butylene terephthalate), cationic dyeable polyamide 6, polyethylene, and Ziegler–Natta isotactic polypropylene 5–15. Polypropylene resins have been produced from Ziegler–Natta catalysts for over 45 years now.…”
Section: Introductionmentioning
confidence: 99%